Comportamento do cimento álcali ativado em ambientes sulfatados - Beltrame, Neusa Aparecida Munhak (2017)
Portland cement (PC) is an industrialized product that is not so consuming of energy and raw materials, but also responsible for large CO2 emissions. Besides the environmental impact, the presence of some hydrated compounds that in contact with the sulfates, produce expansive phases that reduce the useful life of the structures. Minerals additions, such as blast furnace slag, have been added to reduce clinker and increase resistance to sulphates, but not all slags confer employability as addition because of their chemical composition. Cements with additions show very low resistance gain in the early ages, making it uninteresting for the productive chain of civil construction. Thus, the limitations that PC presents, together with the increase of residues, have encouraged the search for clinker-free binders. Alkali-activation provided the possibility of reuse of several by-products, because the reaction kinetics is similar to PC, due to chemical similarity and heat release. Researches related to the durability of alkaliactivated cements (AAC) are still very low, mainly the efficacy of the methods used to evaluate the resistance to sulfates in laboratory environments. Therefore, the objective of this work was to investigate the behavior of slag pastes activated with 5% NaOH and sulfate resistant PC (PCIV-SR) in sulphated environments using the NIST method and to compare with the accelerated mortar method proposed by NBR 13583:2014. The evaluations included microstructural analysis (XRD/SEM/DTG) and macrostructural analysis through visual inspection, dimensional variation, mass variation and compressive strength. The results indicated that under the conditions tested, the accelerated methods of sulfate resistance evaluation did not present significant differences between pastes and mortars. The AACs presented better performance before and after exposure to Na2SO4 compared to PCPIV-SR, favoring hydration and compressive strength. On the other hand, the formation of gypsum appears to be the main degradation product of the AACs in the MgSO4 solution, caused by the C-S-H decalcification, strongly affecting the physical, chemical and mechanical properties of the activated alkali cements.